2017
DOI: 10.3389/fphar.2017.00452
|View full text |Cite
|
Sign up to set email alerts
|

Danshen-Chuanxiong-Honghua Ameliorates Cerebral Impairment and Improves Spatial Cognitive Deficits after Transient Focal Ischemia and Identification of Active Compounds

Abstract: Previously, we only apply a traditional Chinese medicine (TCM) Danshen-Chuanxiong-Honghua (DCH) for cardioprotection via anti-inflammation in rats of acute myocardial infarction by occluding coronary artery. Presently, we select not only DCH but also its main absorbed compound ferulic acid (FA) for cerebra protection via similar action of mechanism above in animals of the transient middle cerebral artery occlusion (tMCAO). We investigated whether oral administration of DCH and FA could ameliorate MCAO-induced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 46 publications
(57 reference statements)
0
28
0
Order By: Relevance
“…The crude ZQ was extracted according to our previously described method ( Zhang et al, 2017a ). Briefly, the ZQ was infiltrated in distilled water (1:12, w/v) for 30 min and boiled twice for 30 min under 100°C.…”
Section: Methodsmentioning
confidence: 99%
“…The crude ZQ was extracted according to our previously described method ( Zhang et al, 2017a ). Briefly, the ZQ was infiltrated in distilled water (1:12, w/v) for 30 min and boiled twice for 30 min under 100°C.…”
Section: Methodsmentioning
confidence: 99%
“…(Danshen)-Carthamus tinctorius L. (Honghua)" is a known herb pair used in ancient traditional Chinese medicine (TCM) prescriptions for ischemic stroke (Li et al, 2013). This herb pair has been used historically in China and other countries in Asia to treat cardiovascular and CVDs (Qin et al, 2009;Liu et al, 2011;Chen et al, 2017b;Zhang et al, 2017b). Danshensu (DSS), salvianolic acid A (SAA), and salvianolic acid B (SAB) are the main hydrophilic components of Danshen (Figure 1) (Li et al, 2018c).…”
Section: Introductionmentioning
confidence: 99%
“…However, the treatment methods for menopausal depression are different. A published study from our colleagues showed that a Chinese medicine, Danshen-Honghua (DSHH), is effective for cognitive deficits after ischemia-induced impairments of the hippocampus [ 14 ]. A wealth of clinical experience has demonstrated that DSHH is very effective in the treatment of menopausal depression.…”
Section: Introductionmentioning
confidence: 99%